Association between exposure in the cement production industry and non-malignant respiratory effects: a systematic review - Anne Kristin Møller Fell; Karl Christian Nordby (BMJ Open)
Objectives Based on findings from a systematic literature search, we present and discuss the evidence for an association between exposure to cement dust and non-malignant respiratory effects in cement production workers.Design and setting Systematic literature searches (MEDLINE and Embase) were performed. Outcomes were restricted to respiratory symptoms, lung function indices, asthma, chronic bronchitis, chronic obstructive pulmonary disease, pneumoconiosis, induced sputum or fraction of exhaled nitric oxide (FeNO) measurements.Participants The studies included exposed cement production workers and non-exposed or low-exposed referents.Primary and secondary outcomes The searches yielded 594 references, and 26 articles were included. Cross-sectional studies show reduced lung function levels at or above 4.5 mg/m3 of total dust and 2.2 mg/m3 of respiratory dust. ORs for symptoms ranged from 1.2 to 4.8, while FEV1/FVC was 1–6% lower in exposed than in controls. Cohort studies reported a high yearly decline in FEV1/FVC ranging from 0.8% to 1.7% for exposed workers. 1 longitudinal study reported airflow limitation at levels of exposure comparable to ∼1 mg/m3 respirable and 3.7–5.4 mg/m3 total dust. A dose–response relationship between exposure and decline in lung function has only been shown in 1 cohort. 2 studies have detected small increases in FeNO levels during a work shift; 1 study reported signs of airway inflammation in induced sputum, whereas another did not detect an increase in hospitalisation rates.Conclusions Lack of power, adjustment for possible confounders and other methodological issues are limitations of many of the included studies. Hence, no firm conclusions can be drawn. There are few longitudinal data, but recent studies report a dose–response relationship between cement production dust exposure and declining lung function indicating a causal relationship, and underlining the need to reduce exposure among workers in this industry.